HEART REMODELING AT DIFFERENT STAGES OF CHRONIC HEART FAILURE IN PATIENTS WITH POSTINFARCTION CARDIOSCLEROSIS AND DILATED CARDIOMYOPATHY - V. V. Mazur; A. M. Kalinkin; E. S. Mazur (Столичная издательская компания, 2016)
Aim. To study the features of cardiac remodeling in patients with dilated cardiomyopathy (DCM) and postinfarction cardiosclerosis (PICS), that can be used for differential diagnosis of these diseases.Material and methods. Patients with DCM (27 men and 5 women; aged 43.1±2.3) and patients with PICS (62 men; aged 56.4±1.1) and chronic heart failure (CHF) were included in the study. The diagnosis of DCM was based on clinical investigation, which also includes coronary angiography. The diagnosis of DCM in 19 patients was proven by the results of postmortem investigation. The diagnosis of PICS was based on documented history of myocardial infarction, ECG and echocardiographic sings. Echocardiography was performed in all patients and 14 healthy volunteers.Results. End-systolic size (ESS) of left ventricular (LV) in patients with DCM and PICS at I (respectively 7.60±0.17 and 7.94±0.18 cm), IIA (7.66±0.28 and 8.64±0.30 cm) and IIB stages of CHF (8.26±0.28 and 8.94±0.15 cm) was significantly more than this in healthy volunteers (6.36±0.16, all p<0.01). ESS of right ventricular (RV) in DCM patients of the same CHF stages (respectively 7.21±0.22, 7.40±0.27 and 8.23±0.27 cm) is also more than this in healthy volunteers (5.95±0.17, all p<0.01). ESS RV in PICS patients at I (5.40±0.11 cm) and IIA (5.80±0.26 cm) CHF stages did not differ from healthy volunteers, and this index risen to IIB stage (6.62±0.21 cm), but was lower than in DCM patients.The ESS LV/ESS RV ratio at any CHF stage in PICS patients was significantly higher than this in DCM patients (1.48±0.04 and 1.06±0.02, 1.50±0.05 and 1.04±0.02, 1.37±0,06 and 1.00±0.01, respectively).Conclusion. The ESS LV/ESS RV ratio can be used for differential diagnosis of dilatation in DCM and PICS patients.